Canonical P elements are transcriptionally active in the saltans group of Drosophila - De Castro, Juliana Polachini [UNESP]; Carareto, Cláudia Márcia A. [UNESP] (Springer Nature, 2004)
Up to now, investigations of expression and regulation of P transposable element have been almost exclusively carried out with the Drosophila melanogaster canonical P element. Analyzing eight species of the saltans group, we detected transposase mRNA in germline tissues of D. saltans and D. prosaltans and repressor mRNA in somatic tissues of D. saltans and D. sturtevanti. Sequencing analysis suggested that these transcripts might belong to the canonical subfamily and that they can be transpositionally active only in D. saltans. dN and dS values of Adh and the P element suggested that the sequences found in D. saltans and D. prosaltans might have been present in the ancestor of the saltans subgroup and that the sequence found in D. sturtevanti might have been horizontally transferred from D. saltans.
Keywords: Drosophila saltans; Horizontal transfer; mRNA; P element; Repressor; Transcription; Transposase; messenger RNA; transposase; animal tissue; controlled study; DNA transposition; Drosophila melanogaster; female; gene control; gene expression; genetic transcription; multigene family; nonhuman; protein analysis; repressor gene; sequence analysis; transposon; Animals; Base Composition; Base Sequence; DNA Primers; DNA Transposable Elements; Drosophila; Gene Components; Gene Expression; Molecular Sequence Data; Phylogeny; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sequence Analysis, DNA; Species Specificity; Animalia; Arachnida; Drosophila prosaltans; Drosophila sturtevanti; Hexapoda; Melanogaster; saltans group; saltans subgroup; transposons